Pendidikan Perempuan Perspektif Quraish Shihab Dalam Tafsir al Misbah - Dhomirotul Firdaus; Zaenal Arifin (Tribakti: Jurnal Pemikiran Keislaman, 2018)
The focus of this article is to discuss how the conception of a woman's position according to M. Quraish Shihab in his book "Tafsir al Misbah". The writing of this article is motivated by the fact that society today still positions women in a marginal position, despite the fact that many Moslems thinkers argue that women have the same dignity as men. And even among certain (urban) communities, women have become drivers of social, economic and political change. But understanding the Indonesian people (especially rural) still positions women in marginal positions. This study generate several conclusions, first, that women's education must be emphasized more on the principle of sharing in improving quality rather than competence to win and lose, continuously empowering, strengthening with religious material, and starting early. Second, according to M. Quraish Shihab women's education is oriented towards material (physical) and immaterial (mind and soul). And third, the paradigm and thought map of M. Quraish Shihab is a critique of the conservative and liberal paradigms, where education should free women from subordination and marginalization due to the discriminative ideology adopted by the people today, as a reflection of religious interpretations of the community against religious teachings, impressive concern for the issue of social injustice, lawsuit for gender discrimination, and social issues.